Evaluation of the English Language Teacher Education Program at the University of Sulaimani - Omer, Tazhan Kamal (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This case study aimed at evaluating the undergraduate English language teacher education program at the University of Sulaimani. To this aim, the strong points and weaknesses of the program were identified as perceived by the students, alumni, and instructors. The participants’ suggestions were also obtained. Additionally, the study investigated whether the program meets the students’ needs or not. As a research design, Peacock’s (2009) model of program evaluation was used and through the student questionnaire, alumni questionnaire, instructor questionnaire, and instructor interviews the data were collected. Hundred and forty-six third and fourth year students, 50 alumni, 15 instructors responded to the questionnaires, and nine instructors participated in the interviews in the present study. The findings of the study showed that the undergraduate English language teacher education program at the University of Sulaimani had several strong points and weak points. The main strength of the program was that it prepared its students to become teachers by teaching them how to teach English and the skills of classroom management. However, the major weak points of the program were insufficient practical opportunities in the courses, unqualified instructors, and having some useless courses in the program. Moreover, the main suggestions that the participants proposed for the program’s improvement were to add more practical courses, to hire qualified teachers, to remove useless courses and to add more language improvement courses, specifically for the first year students before taking the academic courses. Overall, the results of the study showed that the program meets the students’ needs to some extent. The present study has some practical implications such as it may provide useful feedback to the English Department, and help them to make possible changes or revisions in the existing program. Also, some suggestions for further research can be made: to conduct interviews with students, alumni and the other stakeholders (program designers, decision makers, academicians in the field, and Council of Higher Education), and to add observation sessions. Keywords: Program evaluation, language teacher education, language teacher education programs, Peacock’s (2009) model of program evaluation.

ÖZ: Bu durum calışması Sülemaniye Üniversitesi’nin İngiliz dili öğretmen eğitimi lisans programını değerlendirmeyi amaçlamıştır. Bu amaca dayalı olarak öğrencilerin, mezunların ve eğitmenlerin görüşleri alınarak güçlü ve zayıf noktalar tespit ediliştir. Buna ek olarak, bu çalışma programın öğrencilerin ihtiyarçlarını karşılayıp karşılanmadığını araştırmıştır. Araştırma düzeni olarak Peacock’un (2009) program değerlendirme modeli kullanılmış ve öğrenci anketleri, mezun anketleri, eğitmen anketleri ve eğitmen mülakatları yoluyla veri toplanmıştır. Bu çalışmada, yüz kırk altı üçüncü ve dördüncü sınıf öğrencisi, elli mezun, onbeş eğitmen anketleri yanıtlandı ve dokuz eğitmen mülakatlara katıldı. Bu çalışmanın bulguları gösteriyor ki Sülemaniye Üniversitesi’nin İngiliz dili öğretmen eğitimi lisans programının çeşitli güçlü ve zayıf noktaları bulunmaktadır. Bu programın en güçlü yönü öğrencilere nasıl İngilizce öğreteceklerini ve sınıf yönetimi becerilerini öğreterek onları öğretmen olmaya hazırlamasıdır. Bununla birlikte, çalışmanın zayıf noktaları yetersiz uygulama olanakları, niteliksiz eğitmenler ve verilen bazı gereksiz derslerdir. Buna ek olarak, katılımcılar programın iyileştirilmesi için bazı önerilerde bulunmuştur. Mesela daha fazla uygulama derslerinin eklenmesi, nitelikli eğitmenlerin işe alınması, yararsız derslerin programdan kaldırılması ve bölüm derslerine başlamadan önce özellikle birinci sınıf öğrencilerinin dil gelişimi için dersler eklenmesi önerilmiştir. Genel olarak, bu çalışmanın sonuçları programın öğrencilerin ihtiyarçlarını bir dereceye kadar karşıladığını göstermektedir. Bu çalışmanın uygulamaya yönelik bazı önerileri vardır. Örneğin, çalışmanın sonuçları İngilizce Bölümüne yararlı geri bildirim sunmaktadır. Bu geri bildirimler olası değişiklikler yapmak için yardımcı olabilir. Bunun yanında, ileri araştırmalar için bazı öneriler yapılmıştır. Örneğin, öğrencilerle, mezunlarla ve ilgili taraflarla (program tasarımcıları, karar alıcılar, alandaki akademisyenler, ve yüksek eğitim kurulu) mülakatlar yürütülebilir. Ayrıca,ileriki çalışmalara gözlemler eklenebilir. Anahtar kelimeler: Program değerlendirmesi, dil öğretmen eğitimi, dil öğretmen eğitimi programları, Peacock’un (2009) program değerlendirme modeli.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2017. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language Teacher-Education-Study and Teaching-University of Sulaimani; Teachers-Training of-Education Program-Evaluation-University of Sulaimani-Iraq; Program evaluation; language teacher education; language teacher education programs; Peacock’s (2009) model of program evaluation